Creative Thoughts as Acts of Free Will: A Two-Stage Formal Integration. Issue 4 (December 2013) - Simonton, Dean Keith
This article integrates two topics usually considered disciplines apart, namely, creativity and free will. In particular, creative thoughts are conceived as acts of free will. This integration begins by reviewing recent advances in a specific two-stage theory of creative problem solving, namely blind variation and selective retention (BVSR). After discussing the parallel two-stage theory of free will (chance then choice), both two-stage theories are then integrated into a single formal representation entailing choice initial probabilities, final utilities, and prior knowledge values. These three parameters are used to define the creativity of any given solution and the "sightedness" of any generated thought or choice. Both creativity and free will vanish as sightedness increases, but their relation to blindness is more complex, yielding a triangular joint distribution that mandates a second-stage selection or decision process. In addition, to accommodate the need to create choices actively rather than just decide among given choices, the treatment expands to encompass both thoughts and choices as combinatorial products. This extension connects the discussion of free will with both combinatorial models of creativity and the research on the factors that enable a person to engage in free combinatorial processes. The article closes with suggestions of future empirical and theoretical research with respect to psychology, philosophy, and potential future exchanges between the two disciplines.